Chitinase Production by Marine Bacterium Pseudomonas putida Mb12 in Free and Immobilised form: A Comparative Investigation - PAUL, MINI; Amrutha Dinesh; Jyothis Mathew (Fishery Technology, 2023)
The biotechnology sector has taken notice of the better performance of immobilised microbial cells for enzyme production. This promising technology removes the majority of the constraints that free cells experience. In the present study, chitinase production by Pseudomonas putida Mb12 was investigated using both free and immobilised cells. The low-cost prawn shell substrate was used for the optimization of chitinase enzyme production by Ca alginate immobilised P. putida Mb12. Beads made with 3 % Na-alginate, 0.5 M CaCl2, and a curing time of 60 min displayed the highest bead stability and chitinase production. The best conditions for maximal enzyme synthesis by immobilised P. putida Mb12 were found to be 0.5 percent prawn shell powder, 35 °C, pH 6.0, and agitation at 50 rpm. Free bacterial cell, on the other hand, requires agitation at 150 rpm, 40 °C, pH 7.0 and 0.4 percent shrimp shell powder for maximum enzyme production. Immobilised P. putida Mb12 was more resilient to environmental variations such as temperature and pH, retaining 90 % of its peak activity at 30-65 °C and 100 % activity within pH 5-10. Fermentation and thermodynamic parameters suggested that immobilised cells produce 1.5 times more enzyme than free cells. After one month, immobilised P. putida Mb12 retained around 90 % of its initial activity.